Chitosan gel addition in pre-emulsified fish mince - Effect on quality parameters of sausages under refrigerated storage. (August 2019) - Chattopadhyay, Kasturi; Xavier, K.A. Martin; Balange, Amjad; Layana, Porayil; Nayak, Binaya Bhusan
Abstract: Chitosan gel at different concentrations were incorporated into pre-emulsified fish mince for sausage formulations and its effects on functional and physiochemical parameters were evaluated. Water holding capacity of sausage was significantly higher in treatment groups whereas, the pH value was lower in chitosan treated sausages compared to control throughout the storage period. The total volatile basic nitrogen value, free fatty acid content and peroxide value showed slower increase in the treatment groups than the control sample indicating a slower rate of lipid oxidation in chitosan treated sausages while, thiobarbituric acid reactive substances of the chitosan treated samples were slightly higher at elevated doses. Improved textural qualities, lower total viable count and psychrophilic count and better sensory quality substantiate the influence of chitosan in increasing the shelf-life of the sausage. Hence, sausages with 0.25% chitosan gel incorporation could be recommended for best functional and physiochemical attributes in fish emulsion sausages. Highlights: The effect of chitosan gel inclusion in pre-emulsified fish meat was studied. Improved water holding capacity, oxidative stability and textural parameters observed. Acidified chitosan accelerates better microbiological stability. 0.25% chitosan gel inclusion in sausages was found to be ideal for improving quality.